The Impacts of the Team-Assisted Individuality Method Based on Problem-Based Learning and Students Paragraph Writing Skills - Wahyuni, Sinta; Ramadhan, Syahrul; Mukhaiyar, Mukhaiyar; Susmita, Nelvia (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to describe the paragraph-writing skills of the first-semester students at STIFARM Padang before and after implementing the PBL-Based TAI method and analyze the influence of implementing the PBL-based TAI method on the paragraph-writing skills of the first-semester students at STIFARM Padang. This research was quantitative with a descriptive-analytical approach. The population in this research was 210 students of all the first-semester students of STIFARM Padang in the 2023-2024 academic year. Meanwhile, the sample was 60 students of class I2 STIFARM Padang. The instrument used in this research was a performance test. The results showed that first, the persuasive paragraph-writing skills of the first-semester students at STIFARM Padang before the PBL-based TAI method was applied were at a "Enough" qualification (60.09), and after implementing the PBL-based TAI method was in the "Good" qualification (78.98). Furthermore, there is an influence of the PBL-based TAI method on the paragraph-writing skills of the first-semester students at STIFARM Padang. Â